Rancangan Motion Graphic Kampanye Banjir Baleendah - Hafizha, Muhammad Hamas; Persada, Satria Indra Praja (Fakultas Desain Universitas Komputer Indonesia, 2023)
Floods have often occurred in Baleendah District, especially when the rainy season comes. Many factors cause this flood disaster to occur, namely natural factors and human factors, floods caused by human factors often occur because the environment cannot be maintained properly such as people still throwing garbage around watercourses or rivers, lack of water catchment areas. A campaign program is needed to raise awareness and invite the public to jointly prevent floods and protect the environment. Media campaigns through animated motion graphic videos can be a solution to be able to convey a message. This design aims to raise awareness and invite the community to work together to prevent disasters in Baleendah District.